The Structure of Mangrove Community in Sebauk Village, Bengkalis District, Bengkalis Regency, Riau Province - Siregar, Ali Mora Hadamean; Efriyeldi, Efriyeldi; Nasution, Syafruddin (Journal of Coastal and Ocean Sciences, 2022)
The use of mangroves for economic purposes has long been carried out by the community, especially coastal communities without making significant improvements to the mangrove forest. This condition can provide significant pressure to the mangrove ecosystem of Sebauk Village. The purpose of this study is to analyze the community structure of the mangrove vegetation community in Sebauk Village. The method used in this study was the survey method. The result shows that the composition of the mangrove vegetation in Sebauk Village consisted of 3 Species, namely Rhizophora apiculata, Rhizophora mucronata, and Sonneratia alba. The highest inforten index value was Rhizophora apiculata with a percentage of 243.42% and the lowest value was Rhizophora mucronata namely 56.57%. Meanwhile, an informed index value of S. alba was 153.69%.